MODEL HIDROLOGI DAS ITN I - Kustamar, Kustamar (JURNAL SUMBER DAYA AIR, 2018)
Physical spatial factors of watershed such as topography, soil types and land use show a prominent contribution in the distributed water shed modeling. One of the difficulties encountered is the change of topographical information in map form into data that can be read by model program. In the process of analyses, physical spatial factor of water shed is divided into grid system consisting of rectangular cells groups. In each cell, surface run off discharge ,including its direction, is determined based on the depths by applying a one dimension unsteady flow concept whereas direction is determined by using information on four points of the cells. Water depth of the surface run off can be calculated by using both a vertical water movement model and land use area condition. The model has been tested using the available data of Lesti (East Java) watershed. From calibration and verification processes, this so called Hydrological Model of ITN 1 has been successfully applied with very good reliability.